2018
DOI: 10.3389/fpsyt.2018.00057
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Frequency of Cases with Seclusion Is Associated with “Opening the Doors” of a Psychiatric Intensive Care Unit

Abstract: BackgroundImplementing an open door policy is a complex intervention comprising changes in therapeutic stance, team processes, and a change from locked to open doors. Recent studies show that it can lead to a reduction of seclusion and forced medication, but the role of the physical change of door status is still unclear.AimsThe aims of this study is to examine the transition from closed to predominantly open doors on a psychiatric intensive care unit (PICU) and its associations with the frequency of seclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Due to the rising number of cases treated in the UPK, the percentage of involuntary admission decreased from 13.8% in 2000 (33) to 10.6% in 2013–2015. This might have exerted a positive effect on the mean clinical severity of cases and on the therapeutic atmosphere, further supporting the positive effects of the introduction of an open-door strategy in the hospital (22, 28, 29). In total, the frequency of involuntary admissions in our study is within the range found across Europe, with a minimum of 12.4 per 100,000 inhabitants in Italy and up to 232.5 per 100,000 inhabitants in Finland and with considerable national and regional variations (20, 39).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Due to the rising number of cases treated in the UPK, the percentage of involuntary admission decreased from 13.8% in 2000 (33) to 10.6% in 2013–2015. This might have exerted a positive effect on the mean clinical severity of cases and on the therapeutic atmosphere, further supporting the positive effects of the introduction of an open-door strategy in the hospital (22, 28, 29). In total, the frequency of involuntary admissions in our study is within the range found across Europe, with a minimum of 12.4 per 100,000 inhabitants in Italy and up to 232.5 per 100,000 inhabitants in Finland and with considerable national and regional variations (20, 39).…”
Section: Discussionmentioning
confidence: 70%
“…The Psychiatric University Hospital of Basel-Stadt follows a long-term strategy to promote open-door settings in psychiatry (23) and to decrease compulsory measures and stigmatization (10, 26, 27). Accompanying research could show that in the years 2011 onward, the frequency of seclusion and involuntary treatment could be decreased (22, 2830) and that therapeutic atmosphere and patient satisfaction could be increased (7, 31) without noticeable detrimental effects on patients’ and public safety and the provision of mental health-care support (32). In addition, a new legal framework concerning involuntary admission was implemented beginning in January 2013.…”
Section: Introductionmentioning
confidence: 99%
“…105,106 Two interventions had follow-up studies: Initiatives to Reduce Seclusion and Restraint 107,108 and Open Door Policy. [109][110][111] One intervention (Brøset Violence Checklist [112][113][114] ) had been evaluated in a pilot and a subsequent study. In the case of six interventions (Beacon Project, 115,116 Recovery Based Principles, 6,117 Early Recognition Method, 118,119 REsTRAIN Yourself, 22,85,87,120,121 Scottish Patient Safety Programme for Mental Health 91,[122][123][124] and Talk First 83,86,125,126 ), the multiple records related to the same application or study of that intervention, often in different formats.…”
Section: The Distinction Between Records Standalone Interventions Anmentioning
confidence: 99%
“…The earliest enquiry was published in 1999, investigating the effect of a token economy on patient behaviour . The majority of papers in this theme were written from 2014 onwards, reporting on changed ward practices and their influence on coercive practices (such as open and closed wards); regulations and guidelines for practice; and different service configurations …”
Section: Resultsmentioning
confidence: 99%